(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the level of scholarly study of Alisher Navoi’s work “Munshaot”, its source-study and textual features, as well as its linguistic characteristics. The study highlights the role of “Munshaot” in the development of the epistolary genre, its lexical-semantic layers, and stylistic features. In addition, the main directions of scientific research on the work and current research problems in Navoi studies are examined. The results show the necessity of studying “Munshaot” through modern linguopoetic and textual approaches.